Endophytic fungi from Parijoto (Medinilla speciosa) leaves and their potential as biocontrol agents against Corn Pest Larvae - Syaifudin, Andang; Wahidah, Baiq Farhatul (Journal of Natural Sciences and Mathematics Research, 2025)
Parijoto (Medinilla speciosa) leaves are widely used for their antimicrobial properties. Endophytic fungi from these leaves show potential as entomopathogenic agents against Helicoverpa armigera larvae, a moth pest of cotton and corn.The research activities conducted in the laboratory include the isolation and characterization of endophytic fungi, as well as entomopathogenic testing against H. armigera larvae using a spraying technique with endophytic fungal extracts. In this study, 5 isolates were obtained from leaves and assessed their entomopathogenic properties. The isolate code is EP1, EP2, EP3, EP4, EP5. Bioassays were conducted to evaluate the effectiveness of these fungi in controlling H. armigera larvae. Among the tested fungi, EP5 demonstrated the highest entomopathogenic activity, significantly reducing the survival rate of the larvae. These findings indicate that EP5 holds substantial promise as a biocontrol agent for managing H. armigera populations with mortality percentage 30,78%, offering a sustainable and environmentally friendly alternative to chemical pesticides. The study underscores the potential of utilizing endophytic fungi from parijoto leaves in integrated pest management strategies.